Universal Kit for Split Inverter Air Conditioner - Taradeh, Yousri Ibraheem; Abusaif, Omar Yousif (جامعة بوليتكنك فلسطين - اتمتة صناعية, 2017)
The objective of this Project is to search for an efficient way for solve the problems in modern air conditioner, Focusing at A huge maintenance cost in comparison to the cost of the device and Replacing the panel inverter by another make. Universal Kit for Split Inverter Air Conditioner low cost; a new kit was designed to alternative board that can be replaced on various types of modern split inverter air conditioners. the project contains two main boards of the split inverter HVAC, Indoor and Outdoor board, in the indoor board human machine interface, communication parts and the fan driver. While Outdoor board contains rectifier, insulation component, protection circuits, filters and multi power drives boards.
CD, no of pages 37,اتمتة صناعية 8/2017, in the store
Keywords: Universal Ki, Split Inverter ,Air Conditioner